Expansion of the genus Massinium (Holothuroidea: Thyonidae) to the American continent and description of a new species - Solís-Marín, Francisco-A. (2021)
Introduction: The genus Massinium includes 11 species, most from the Indo Pacific Ocean, and had not previously being reported from the American continent. Objective: To present the new record of the genus Massinium and describe a new species of this genus. Methods: Material collection was done by SCUBA-diving to depths of a maximum of 9 m. Results: Massinium ocumichoensis sp. nov. is described from seven specimens that extends the range of the genus to the American continent (Guerrero, Michoacan and Jalisco, Mexico). The new species lives in sandy-rocky substrata, from 2 to 16 m deep. It is distinguished from its congeneric species by a combination of morphological characters: mid-dorsal slightly bigger pseudobuttons (40-60 μm), and tables in the body wall. A taxonomic key for distinguishing the species of Massinium is provided. Conclusions: The geographic range of the genus Massinium is extended to the Mexican Pacific with M. ocumichoensis sp. nov.